दर्शन र साहित्य Philosophy and Literature - गड्तौला Gadtaula नारायण Narayan (Vangmaya वाङ्मय, 2022)
दर्शन र साहित्य ज्ञानका भिन्न शाखा हुन् । दर्शन ज्ञानप्रधान बौद्धिक वाङ्मय रूप हो भने साहित्य आह्लाद प्रधानरागात्मक वाङ्मय कला हो । तत्वमीमांसा र ज्ञानमीमांसाको विमर्शमा केन्द्रित दर्शनविधा तर्क एवं कार्यकरणको वस्तुनिष्ठ भाषामा व्यक्त हुन्छ भने साहित्य जीवन जगत्कै सत्यतथ्यलाई कल्पनाको जलपले रङाएर आलङ्कारिक, विरोधाभाषी, लक्षणाव्यञ्जनामूलक भाषामा व्यक्त हुन्छ । यी दुई वाङ्मयका भिन्न विधा भए पनि दर्शन साहित्यबाट अभिव्यक्ति कलाको अपेक्षा गर्दै थोरै कलाको सम्पुटनबाट सम्प्रेष्यताको आलोक प्राप्त गर्दछ भने साहित्य दर्शनको वैचारिकतालाई अन्तःगर्भमा लुकाएर किञ्चित् बौद्धिक तुष्टि प्रदान गर्दछ । Philosophy and literature are two different branches of knowledge. Philosophy is acknowledge-oriented intellectual rhetoric form while literature is an ecstatic melodic rhetoric art. Philosophy centers on the discussion of metaphysics and epistemology, which is expressed in the objective language of logic and causality. Literature, however, is expressed in figurative, contradictory and allegorical language by painting the realities of the world of life with the plated of imagination. Although these two genres of rhetoric are different, philosophy receives the light of communicativeness from the collection of art, expecting art of expression from literature, while literature provides a little intellectual satisfaction by hiding the ideology of philosophy in the womb. In this kind of interrelationship, one can see the interdependent relationship between philosophy and literature. The main purpose of this article is to study that relationship. For that, the data has been collected through library work and analyzed in a descriptive and explanatory method. Analyzing the relationship between philosophy and literature in this article, it has been concluded that philosophy is a branch of knowledge-oriented, objective, intellectual, causal, factual rhetoric and literature is a branch of rhetoric based on sentimental, heartfelt, subjective, imaginary truth.